Amalan pengajaran guru di Pondok Bantan, Nakhon Si Thammarat, Thailand - Mohd Aderi Che Noh (Tanjong Malim, 2019)
Amalan pengajaran guru di Pondok Bantan, Nakhon Si Thammarat, Thailand by Mohd Aderi Che Noh